Improvement in walking abilities in transfemoral amputees with a distal weight bearing implant. (February 2017) - Guirao, Lluis; Samitier, C Beatriz; Costea, Maria; Camos, Josep Maria; Majo, Maria; Pleguezuelos, Eulogio
Background: The ability to walk with a prosthesis is the main objective of rehabilitation following amputation, and distance and speed of walking achieved are considered determining factors in amputees' perception of quality-of-life. Objectives: To assess walking abilities and improvement in gait distance and speed parameters in patients undergoing transfemoral amputation with a femoral implant that allows distal support of the residuum. Study design: Experimental before-and-after study. Methods: Ten transfemoral amputation patients received a titanium implant that allowed distal weight bearing of the residuum within the socket. The post-intervention follow-up period was 14 months. We evaluated the functionality using a 2-min walk test and the physiological cost index. Results: The etiology of amputation was traumatic in six patients (60%). The mean 2-min walk test score was 98.4 ± 19.5 m prior to the femoral implant and 122.5 ± 26.1 m at 14 months ( p < 0.008), representing an improvement of 24.5%. The mean gait speed prior to the femoral implant was 0.82 ± 0.16 and 1.02 ± 0.21 m/s at 14 months ( p < 0.008). The physiological cost index showed no differences ( p < 0.55). Conclusion: The results of this study show an improvement in the distance walked and gait speed in amputees 14 months after having received a femoral implant. Clinical relevance: This article provides additional insight into the use of a femoral implant that allows distal support of the residuum to improve walking abilities and gait distance and speed parameters in patients undergoing transfemoral amputation, mainly those of vascular origin.